The BFG - Dahl, Roald; Illustrated By Blake, Quentin (London Puffin Books, 2013)
Every night, when the world is sleeping, big gruesome giants guzzle up whoppsy-whiffling human beans. And there's only one giant who can stop them - the BFG. He's the kindest giant there is and, with his friend Sophie in his top pocket, he sets out to rid the world of the Bloodbottler, the Fleshlumpeater and all their rotsome friends forever...The well-loved story of a big friendly giant celebrates its 30th anniversary with a right royal new cover by Quentin Blake! Roald Dahl, the best-loved of children's writers, was born in Wales of Norwegian parents. After school in England he went to work for Shell in Africa. He began to write after "a monumental bash on the head", sustained as an RAF pilot in World War II. Roald Dahl died in 1990. Quentin Blake is one of the UK's most celebrated artists, renowned for his collaboration with Roald Dahl. He is visiting Professor at the Royal College of Art and lives in London.
Include Illustrations
Keywords: Giants -- Orphans -- Children's Stories, English